2021
DOI: 10.1016/j.jpba.2021.114064
|View full text |Cite
|
Sign up to set email alerts
|

Urine proteome changes in a chronic unpredictable mild stress (CUMS) mouse model of major depressive disorder

Abstract: Background. Major depressive disorder (MDD) is a prevalent complex psychiatric disorder with a high prevalence rate. Because MDD is a systemic multifactorial disorder involving complex interactions and disturbances of various molecular pathways, there are no effective biomarkers for clinical diagnosis. Urine is not subjected to homeostatic control, allowing it to reflect the sensitive and comprehensive changes that occur in various diseases. In this study, we examined the urine proteome changes in a CUMS mouse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…The chemical examination of urine includes the identification of protein, blood cells, glucose, pH, bilirubin, urobilinogen, ketone body, nitrite, and white blood cells esterase ( 3 , 4 ). Urine can also sensitively detect the pathological alterations that occur in various diseases ( 5 ), such as bladder and prostate cancer ( 6 , 7 ). In contrast, the macroscopic aspects refer to the color and cloudiness analyses ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…The chemical examination of urine includes the identification of protein, blood cells, glucose, pH, bilirubin, urobilinogen, ketone body, nitrite, and white blood cells esterase ( 3 , 4 ). Urine can also sensitively detect the pathological alterations that occur in various diseases ( 5 ), such as bladder and prostate cancer ( 6 , 7 ). In contrast, the macroscopic aspects refer to the color and cloudiness analyses ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, OPN concentrations did not differ significantly, as the OPN level (ng/mL) in the study group was 57.0 (15.9), while in the control group, it was 56.3 (12.5) [44]. Proteomic analysis of urine in a mouse model of major depressive disorder (MDD) under chronic unpredictable mild stress (CUMS) showed a decrease in OPN levels in the study group [45]. It is also worth noting a study conducted on cell cultures, which showed that treatment with valproic acid results in an increase in OPN expression after only 4 days of treatment [46].…”
Section: Opn In Psychiatrymentioning
confidence: 97%
“…Relative quantification by liquid chromatography-tandem mass spectrometry ( LC-MS / MS ) is a promising protein biomarker identification technique. Proteomics analysis shows that there are considerable pathophysiological changes in depression [3,4] , Alzheimer 's disease [5] , Parkinson 's disease [6] and other mental systemic diseases. The purpose of this study is to explore whether urinary proteomics has the potential to identify objective diagnostic markers of schizophrenia, whether it can distinguish between patients and normal people from the perspective of urinary proteomics, and provide clues for clinical diagnosis and other related biomarkers.…”
Section: Introductionmentioning
confidence: 99%